2022
DOI: 10.1017/s0950268822001522
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem inflammatory syndrome associated with SARS-CoV-2 infection in children: update and new insights from the second report of an Iranian referral hospital

Abstract: Introduction: Here, we are sharing our second report about children affected by Multisystem Inflammatory Syndrome in Children (MIS-C). The aim of the present study was to update our knowledge about children with MIS-C. Furthermore, we tried to compare clinical manifestations,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…The deficit of 25-OH vitamin D is a major health issue; it is estimated that over a billion people worldwide lack 25-OH vitamin D [ 14 ]. Although there were few studies in the beginning, a link between symptomatology, severity and outcome in COVID-19 with regard to 25-OH vitamin D has been observed [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The deficit of 25-OH vitamin D is a major health issue; it is estimated that over a billion people worldwide lack 25-OH vitamin D [ 14 ]. Although there were few studies in the beginning, a link between symptomatology, severity and outcome in COVID-19 with regard to 25-OH vitamin D has been observed [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Torpoco Rivera et al ( 20 ), the authors found that the seriousness of MIS-C, especially cardiac involvement, was associated with severe vitamin D deficiency [25 (OH) vitamin D level <10 ng/mL]. In the study conducted by Mamishi et al ( 21 ), 122 patients with MIS-C were divided into two groups (mild-moderate and severe). Mild-to-moderate MIS-C was present in 97, while severe MIS-C was present in 25.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, there are many therapeutic approaches, which include agents with direct action such as antivirals (remdesivir, favipiravir, lopinavir/ritonavir, molnupiravir, nirmatrelvir/ritonavir, simeprevir), antimalarials (chloroquine, hydroxychloroquine), antibiotics (azithromycin), or with supportive action, such as interleukin inhibitors (anakinra, tocilizumab), Janus kinase inhibitors (baricitinib), corticotherapy (dexamethasone), anticoagulants (low molecular weight heparin) and non-steroid anti-inflammatory drugs. Information about treatment options for children is somewhat scarce, however it is known that remdesevir and nirmatrelvir/ritonavir were approved for use, while the use of lopinavir/ritonavir was discouraged in pediatric patients [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%